Eksistensi Transmisi Budaya Terhadap Perkembangan Institusi Pendidikan di Era Society 5.0 - Kurniawati, Elvia; F, Firman; Sukma, Dina; Suharnadi, Putra (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research examines the important role of cultural transmission in the development of education in society 5.0. The main focus of the research is to analyze how cultural values are transmitted through the education system and their impact on the cognitive, social and emotional development of students. The method used in this research is a literature study by examining various sources. This research analyzes how cultural values can be maintained and transmitted in an increasingly digital and automated education system. The results of the study show that the integration of technology in education needs to be balanced with strengthening local cultural values to create a balance between technological progress and preserving cultural identity.